Analysis and analytic techniques in African music: A theory of melodic scales - Ekwueme, Lazarus (International Library of African Music, 1980)
In our present study, we intend to show that a systematic analysis of the music of black Africa reveals an internal structural government of extraordinary order and symmetry. This study deals with the theory of melodic scales. Our examples will be taken from one area of Africa, the music of the Igbo of Nigeria; we have, however, shown elsewhere that examples of the same or a similar system operating in the music of other areas of black Africa abound in large numbers.
Keywords: African Music